2006
DOI: 10.1227/01.neu.0000215950.85745.33
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the Craniovertebral Junction: Is Surgery Necessary?

Abstract: The mainstay of management of tuberculosis of the craniovertebral junction is prolonged antitubercular treatment with a rigid external immobilization. Surgery is not necessary, even in patients with advanced stages of disease. Complete clinical and radiological healing occurs in all patients with conservative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 12 publications
1
71
0
1
Order By: Relevance
“…Literature is quite divided on management of patients with tuberculosis involvement of the craniovertebral junction [4,7,[9][10][11][12]14]. Some people recommend conservative treatment only [1,2,5,11,22], others recommend surgery in all patients [3,6,8,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature is quite divided on management of patients with tuberculosis involvement of the craniovertebral junction [4,7,[9][10][11][12]14]. Some people recommend conservative treatment only [1,2,5,11,22], others recommend surgery in all patients [3,6,8,23].…”
Section: Discussionmentioning
confidence: 99%
“…Others come to the conclusion that surgery is not necessary in craniocervical junction tuberculosis [14], since finally all patients will clinically heal as well as radiologically under conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis may be difficult and management can be challenging, requiring different treatment modalities depending on the clinical symptoms or radiological features. Treatment options are also controversial without well-defined guidelines, including a conservative approach (anti-tuberculosis medication and external fixation), relatively simple surgery (posterior fusion and fixation), or radical surgery (debridement, decompression and stabilization) [1][2][3][4][6][7][8][9][10][11][12][13][15][16][17][18]20) . The authors present a case of CVJ tuberculosis with atlantoaxial dislocation (AAD) and retropharyngeal abscess.…”
Section: Introductionmentioning
confidence: 99%
“…13 In cranio-vertebral junction tuberculosis, despite extensive erosion of the clivus, C1 and C2, and spinal cord compression, the patients can effectively be managed with antituberculosis therapy alone. 9,16 We could deduce that significant cord compression and spinal extension of abscess were significantly associated with outcome in cervical spine tuberculosis. These observations indicated that extensive tuberculous involvement of the spinal cord was responsible for the poor outcome.…”
Section: Discussionmentioning
confidence: 94%